An Efficient Route to Highly Substituted Indoles via Tetrahydroindol‐4(5H)‐one Intermediates Produced by Ring‐Opening Cyclization of Spirocyclopropanes with Amines. Issue 66 (5th September 2017) - Nambu, Hisanori; Hirota, Wataru; Fukumoto, Masahiro; Tamura, Takafumi; Yakura, Takayuki
Abstract: An efficient route to highly substituted indoles was developed. It included regioselective functionalization of tetrahydroindol‐4(5 H )‐ones, prepared by ring‐opening cyclization of cyclohexane‐1, 3‐dione‐2‐spirocyclopropanes with primary amines, and subsequent oxidation. The 6‐substituted indoles were synthesized from a readily available 5‐substituted cyclohexane‐1, 3‐dione‐2‐spirocyclopropane. The synthesis of 5‐ and 7‐substituted indoles was achieved by regioselective electrophilic alkylation of tetrahydroindol‐4(5 H )‐one, followed by oxidation. The 4‐substituted indoles were synthesized by nucleophilic alkylation of the corresponding pyrrole derivative, which was prepared by partial oxidation of tetrahydroindol‐4(5 H )‐one, and sequential oxidation. The synthesis of 4‐substituted indoles was also accomplished by palladium‐catalyzed coupling of 4‐hydroxyindole‐derived triflates. Furthermore, the synthesis of 4, 5, 6, 7‐tetrasubstituted indoles was achieved by using these regioselective alkylations. Abstract : Ringing in the changes : The synthesis of 5‐ and 7‐substituted indoles was achieved by regioselective alkylation followed by oxidation to indoles, whereas the 4‐substituted indoles were synthesized by oxidation to the pyrrole derivative, alkylation with alkyllithium, and oxidation to the indole (see scheme; LDA=lithium diisopropylamide, LiHMDS=lithium hexamethyldisilazide).